2009
DOI: 10.1158/1541-7786.mcr-09-0319
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of MicroRNAs by Type I IFN through the Activation of Signal Transducers and Activators of Transcription 3 in Human Glioma

Abstract: Type I IFNs are involved in double-stranded RNA responses. Here, we investigated the possibility that IFN-β may induce or downregulate cellular microRNAs (miRNA) in human neoplasms and thereby use the RNA interference system to show antitumor effects. Because of its known connection to glioma biology, we focused on miR-21 among seven miRNAs influenced by IFN-β. We analyzed the effect of IFN-β treatment on miR-21 expression in glioma cells and intracranial glioma xenografts. IFN-β treatment reduced miR-21 expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
2
43
2
Order By: Relevance
“…Moreover, STAT3-driven miR-21 transactivation was found in other types of cancer, such as prostate cancer (16), glioma (50), and colon cancer (51), in response to IL-6 or IFN treatment. Our data suggested that IL-6-dependent STAT3 activation also promotes miR-21 transcription in breast cancer cells upon genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STAT3-driven miR-21 transactivation was found in other types of cancer, such as prostate cancer (16), glioma (50), and colon cancer (51), in response to IL-6 or IFN treatment. Our data suggested that IL-6-dependent STAT3 activation also promotes miR-21 transcription in breast cancer cells upon genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C). This finding supports the studies by others 36,43,44 showing that IFN-␣/␤ is the potent inducer of miRNAs in several cell systems. However, this IFN-mediated anti-HIV innate immunity in monocytes was dampened by morphine treatment (Figure 2C).…”
Section: Discussionsupporting
confidence: 92%
“…1a,b) 20 . Both IFNs and nuclear factor-kB cascades activate the STAT3/Myc/ Lin28B axis, repressing expression of miRNAs from the let-7 family 18,[21][22][23] . Indeed, in HeLa cells, 24-h IFNa treatment inhibited let-7i and let-7g expression by 80 and 60%, respectively, while miR-21 was unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%